Pembuatan Disinfektan dari Bahan Alami untuk Meminimalisir Penularan Covid-19 - Budiman, Budiman; Arisman, Anugrah Yusuf; Sulfidar, Sulfidar; Arsyad, Muhammad (Wellness And Healthy Magazine, 2020)
This research was conducted to produce disinfectants made from natural aims to reduce Covid-19 transmission for people who are less able. Where in minimizing the spread of one of them washing hands using disinfectants. The results of the research are betel leaf, lemon, and water can be made in preparation as a disinfectant. This research was carried out through various sources including books, the internet, and journals and research by others. It is expected that the results of this study can provide education to the public so that they maintain better health and personal hygiene to reduce the increase in the spread of Covid-19, especially in Indonesia.